Group and Cipher in Wormhole and Quantum Entanglement (European Journal of Pure and Applied Mathematics, 2021)
In this article, we present wormholes cryptosystems (WCS). The first is the wormhole key distribution centre theorem, which asserts that the WCS is a public key group. The second is the security theorem, which asserts that the WCS are a one-way function. The third is new version of the definition for the WCS, and we introduce the notion of groups of WCS. The fourth ingredient is the encryption algorithm and decryption algorithm, and design principle. Here, we present a toy example to illustrate the computation of these encryptions and decryptions. The finally we present the unsymmetrical WCS theorem.
Keywords: $pa$-group; one-way function; quantum entanglement; wormhole; cryptography